Smart specialization policies: innovative performance models from European regions - Lopes, João (2019)
Submitted by Luis Farinha (luis.farinha@ipcb.pt) on 2018-12-27T15:39:08Z No. of bitstreams: 1 Lopes-2018-Smart-specialization-policies-innov (1).pdf: 1343471 bytes, checksum: d300bbf5596b2b0c2e1a8980a8db2e1e (MD5)